2020
DOI: 10.3847/1538-3881/ab536b
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Evolutionary History of Comets: An Investigation of the Hypervolatiles CO, CH4, and C2H6 in the Jupiter-family Comet 21P/Giacobini–Zinner

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…It is clear from Figure 1 that the asymmetric activity is seen for all species and this behaviour does not change over the various apparitions (Schleicher et al 1987;Combi et al 2011) as shown also in Figure 2 for the water production rate. The same behavior has been reported for the parent molecules (H 2 O, CO, CH 4 , C 2 H 2 , C 2 H 6 , NH 3 and CH 3 OH) production rates derived at infrared wavelengths during the 2018 passage (Faggi et al 2019;Roth et al 2020). This might due to the shape of the nucleus and its spin-axis orientation.…”
Section: Gas Production Ratessupporting
confidence: 80%
See 1 more Smart Citation
“…It is clear from Figure 1 that the asymmetric activity is seen for all species and this behaviour does not change over the various apparitions (Schleicher et al 1987;Combi et al 2011) as shown also in Figure 2 for the water production rate. The same behavior has been reported for the parent molecules (H 2 O, CO, CH 4 , C 2 H 2 , C 2 H 6 , NH 3 and CH 3 OH) production rates derived at infrared wavelengths during the 2018 passage (Faggi et al 2019;Roth et al 2020). This might due to the shape of the nucleus and its spin-axis orientation.…”
Section: Gas Production Ratessupporting
confidence: 80%
“…This could be due to a sensitivity issue in their data as the production rates seem to level off on both sides of perihelion while the distance increase or to a higher activity level of the comet after perihelion in the past. It has been also found that there is no significant change in the production rates of hypervolatile molecules (CO, CH 4 , and C 2 H 6 ) in comet 21P over the three different apparitions, 1998 (Weaver et al 1999;Mumma et al 2000(DiSanti et al 2012) and 2018 (Faggi et al 2019;Roth et al 2020).…”
Section: Gas Production Ratesmentioning
confidence: 93%
“…Taking this change into account, one can infer that the comet activity follows the same trend as in 1998 of continuous decrease of active surface around perihelion. This was also observed by Combi et al (2011) and Roth et al (2020) for the 1998, 2005, and 2018 perihelions. Besides this small trend, production rates and relative abundances were very similar in 1998 and 2018, suggesting no significant secular trend both in activity and composition.…”
Section: Evolution Of Production Rates Of Comet 21psupporting
confidence: 72%
“…This was also observed for the visual heliocentric magnitude, which peaked 1-2 weeks prior to perihelion in 1998 and 2018. In 2018, Roth et al (2020) observed OH and H 2 O in the infrared yielding a water production rate in the range 3.2-3.0 × 10 28 molec. s −1 for the 7-11 September period, just before our IRAM observations.…”
Section: Reference Water Production Ratementioning
confidence: 99%
“…However, as noted above, the statistics for CH in JFCs are far from robust. Recent years have provided several rare and favorable opportunities to observe CH in JFCs [ 52 , 110 , 111 , 112 , 113 , 114 ], providing a much needed boost towards establishing a statistically significant sample of CH measurements in JFCs. However, it is still much smaller than the OCC sample, making comparisons between the two classes more difficult.…”
Section: Results For Specific Speciesmentioning
confidence: 99%